Fire has little to no effect on the enhancement of germination, but buried seeds may survive in a Neotropical wetland - Soares, Vanessa C.; Scremin-Dias, Edna; Felipe Daibes, L. [UNESP]; Damasceno-Junior, Geraldo A.; Pott, Arnildo; Lima, Liana B. de (Elsevier B.V., 2021)
Contrasting responses of seed germination to fire have been reported in different vegetation worldwide. In Brazil, the Pantanal harbors one of the world?s most extensive floodplains, marked by flooding periods alternating with a dry fire-prone season. The present study aimed to understand the role of fire on regeneration from seed in the Pantanal wetland, using two pioneer species displaying physically dormant seeds as study models: Sesbania virgata (Cav.) Pers. and Guazuma ulmifolia Lam. Seeds were subjected to (1) heat shocks and (2) experimental burns, besides the controls. In Experiment 1, heat shocks of 65, 85, 105, 125, and 145?C (all treatments ? 5?C), were applied for 5 minutes of exposure. In Experiment 2, seeds and corky fruits were placed upon the soil surface, and seeds were buried at 2 cm belowground, then subjected to experimental burns. Germination trials were conducted under optimal conditions and recorded the proportions of germinated, hard, and dead seeds. Increasing temperature of heat shocks had an increasingly negative effect on seed water content and germination of both species as well as increasing the proportion of dead seeds. A slight enhancement in germination of buried seeds (18%) was found in the experimental burns for S. virgata seeds. Moreover, buried seeds remained hard (dormant) up to 80 and 40% for S. virgata and G. ulmifolia, respectively. Inside the corky fruits, seed germination was not promoted, and there was a decrease in the proportion of hard seeds after burning, while direct exposure to fire killed nearly all seeds placed upon the soil surface. Fire has little to no effect on the enhancement of seed germination, but seeds mainly survive when buried belowground. Our study provides crucial information to understand seed tolerance to increased fire occurrence in disturbed tropical wetlands.
Keywords: Guazuma; Heat shock; Physical dormancy; Pantanal; Riparian forest; Sesbania